Ipsilateral humeral neck and shaft fractures - Zhu, Bin; Micić, Ivan; Kim, Kyung-Chun Kim; Park, Jin-Young; Kekatpure, Aashay; Stojiljković, Predrag; Jeon, In-Ho (Vojnosanitetski pregled, 2017)
Background/Aim. Fractures of the proximal humerus or shaft are common, however, ipsilateral neck and shaft humerus fracture is a rare phenomenon. This combination injury is challenging for orthopaedic surgeons because of its complex treatment options at present. The purpose of this study was to review a series of ipsilateral humeral neck and shaft fractures to study the fracture pattern, complications and treatment outcomes of each treatment options used. Methods. A total of six patients (four female and two male) with the average age of 42.8 years (range: 36–49 years) was collected and reviewed retrospectively. Two of them were treated with double plates and four with antegrade intramedullary nail. According to the Neer’s classification, all proximal fractures were two-part surgical neck fractures. All humeral shaft fractures were located at the middle of one third. Five fractures were simple transverse (A3), one fragmented wedge fracture (B3). One patient had associated radial nerve palsy. Results. All surgical neck fractures except one united uneventfully in the average time span of 8.7 weeks. Four humeral shaft fractures healed in near anatomic alignment. The remaining two patients had the nonunion with no radiological signs of fracture healing. The average University of California, Los Angeles End-Results (UCLA) score was 23.1. On the contrary, the average American Shoulder and Elbow Surgeon's (ASES) score was 73.3. The patients treated with antegrade intramedullary nails presented 70.5 points. The ASES scores were 79 in the double plates group. Conclusions. Ipsilateral humeral shaft and neck fracture is extremely rare. Both antegrade intramedullar nailing and double plates result in healing of fractures. However the risk of complication is lower in the double plating group.
Keywords: humeral fractures; fractures; multiple; fracture fixation; intramedullary; bone plates; treatment outcome